132k views
2 votes
Without actual division prove that x4 +2x3 -2x2 +2x -3 is exactly divisible by
x2 +2x-3

User Dave Ward
by
5.1k points

1 Answer

5 votes

Answer:

Step-by-step explanation:


\displaystyle\Large\boldsymbol{} x^4+2x^3-2x^2+2x-3= \\\\\\x^4+2x^2(x-1)+2x-\underbrace{2-1}_(-3)= \\\\\\x^4-1+2x^2(x-1)+2x-2 = \\\\\\(x^2-1)(x^2+1)+2x^2(x-1)+2(x-1) = \\\\\\\underline{(x-1)}(x+1)(x^2+1)+2x^2\underline{(x-1)} +2\underline{(x-1)} =\\\\\\(x-1)((x+1)(x^2+1)+2x^2+2)=\\\\\\(x-1)(x^3+x^2+2x^2+x+2+1)=\\\\\\(x-1)(x^3+3x^2+x+3) =\\\\\\(x-1)( \underline{(x+3)}x^2+\underline{(x+3)})=(x^2+1)\underbrace{(x-1)(x+3)}_(x^2+2x-3)= \\\\\\(x^2+1)(x^2+2x-3) : (x^2+2x-3)=x^2+1

User Suulisin
by
5.3k points